Trap‐Assisted Triplet Emission in Ladder‐Polymer‐Based Light‐Emitting Diodes. (19th March 2020) - Khodabakhshi, Elham; Ramanan, Charusheela; Michels, Jasper J.; Bonus, Sven; Hertel, Dirk; Meerholz, Klaus; Forster, Michael; Scherf, Ulrich; Blom, Paul W. M.
Abstract: The charge transport and recombination in light‐emitting diodes (LEDs) based on a methyl‐substituted poly( p ‐phenylene) ladder polymer (Me‐LPPP) are investigated. The transport is characterized by a high room‐temperature hole mobility of 2 × 10 −8 m 2 V −1 s −1 combined with anomalously strong electron trapping. Their electroluminescence (EL) spectrum is characterized by a blue singlet emission, a broad green featureless peak, and a yellow‐orange triplet emission. The voltage dependence of the EL spectrum and negative contribution to the capacitance indicate that the triplet‐emission is of trap‐assisted nature, consistent with the strong electron trapping. Consequently, the color purity of the blue emissive Me‐LPPP polymer LEDs can be strongly improved using trap dilution. Abstract : The electroluminescence spectrum of light‐emitting diodes (LEDs) based on a methyl‐substituted poly( p ‐phenylene) ladder polymer (Me‐LPPP) is characterized by a blue singlet emission, a broad green featureless peak, and a yellow‐orange triplet emission. Since the triplet emission is of a trap‐assisted nature, the color purity of the blue emissive Me‐LPPP polymer LEDs can be strongly improved using trap dilution.